The Correlation Between the Students’ Writing Motivation and the Writing Ability - Aryanika, Septa (English Education: Jurnal Tadris Bahasa Inggris, 2016)
The objectives of this research are to know the level of the students’ writing motivation, to know the level of the students’ writing ability, and to know whether there is any positive and significant correlation between the students’ writing motivation and the writing ability among the eleventh grade students of Senior High School Utama Wacana Metro in the academic year of 2009/2010.This research was conducted at the eleventh students of Senior High School Utama Wacana Metro. The population of this research consist of 136 students. And the sample consists of 52 students. It is established through the simple random sampling technique. The instruments used in this research are questionnaire and test. The writer used questionnaire to know the levels the students’ writing motivation. Furthermore, to know the level of the writing ability, the writer used writing test. To analyze the data, the writer used product moment correlation. The result of data analysis is “r observed” = 0, 506 higher than “r table” = 0, 273.  Based on the result of analysis data above, it can be inferred that Ha is accepted.